Biodegradation Test of Polluted River Caused by Domestic Wastewater Using Indigenous Bacteria in the Way Tomu Watershed, Ambon City (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Nowadays, the rivers are often used by residents around the river as the final disposal of domestic wastewater that causes the rivers to become polluted. Biodegradation is an alternative to wastewater treatment as an effort to solve water pollution which is often carried out using bacteria that have the potential to decomposers in the biodegradation process, especially indigenous bacteria. This study aims to identify and obtain isolates, combinations, and characteristics of the indigenous bacteria isolate that have the potential as a biodegradation agent for polluted river caused by domestic wastewater in the Way Tomu watershed, Ambon City. In this study, isolates of indigenous bacteria that were isolated and purified were tested for protease and amylase enzyme activity to select isolates to be used in the biodegradation process testing consisting of parameters pH, COD, and TSS as indicators of the biodegradation. Afterward, the isolates that have the best potential as biodegradation agents will be characterized and biochemical tests will be carried out to identify the general characteristics of these isolates. The results showed that the combination of Genus Aeromonas, Bacillus, and Pseudomonas as isolates of indigenous bacteria that has the best potential as an agent for the biodegradation of polluted river caused by domestic wastewater. The benefit of this research is as initial information and consideration for alternative treatment of polluted rivers caused by domestic wastewater using indigenous bacteria isolates as an effort to resolve river pollution, especially the rivers in Ambon City.